Evaluation of the effects a caregiver training programme has on the cognitive and functional maintenance of the elderly / Valoración de los efectos de un programa de formación de cuidadores sobre el mantenimiento cognitivo y funcional de ancianos. Issue 2 (2nd September 2018) - Sanjuán, Miriam; Calero, María-Dolores; Abarca, Silvia; Navarro, Elena
Abstract: With the increase in the elderly population comes a need to ensure they remain cognitively and functionally stable for as long as possible. Achieving this through a caregiver training programme based on the Person Centred Care (PCC) approach has been suggested. On this basis, the purpose of this study has been to evaluate the effectiveness of a caregiver training programme on the cognitive and functional maintenance of the elderly. The study sample comprised 56 elderly people and 14 caregivers, who were assessed using the MMSE, Clifton, Barthel, EuroQol, RMBPC (elderly) and SSFQ (caregivers) measurement scales. The results at intergroup level show significant differences in the pre-treatment assessment: the control group had higher scores for MMSE, Barthel, EuroQol and RMPBC scales, but that difference disappeared as scores for the treatment group increased. At an intragroup level, increases in scores were observed in the MMSE, Clifton and EuroQol scales for the treatment group and decreases in the Clifton, EuroQol and Barthel scales for the control group. From these results we can conclude that a caregiver training programme based on a PCC approach produces cognitive and functional benefits in the elderly. In addition, caregivers in the treatment group felt more competent, confident and satisfied with their work.